2013
DOI: 10.1080/02626667.2013.778411
|View full text |Cite
|
Sign up to set email alerts
|

Effect of modelling scale on the assessment of climate change impact on river runoff

Abstract: The effect of using two distributed hydrological models with different degrees of spatial aggregation on the assessment of climate change impact on river runoff was investigated. Analyses were conducted in the Narew River basin situated in northeast Poland using a global hydrological model (WaterGAP) and a catchment-scale hydrological model (SWAT). Climate change was represented in both models by projected changes in monthly temperature and precipitation between the period 2040-2069 and the baseline period, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 43 publications
1
10
0
Order By: Relevance
“…Some regional trends can even be opposite to the overall trend for large areas (Arheimer et al 2012), and some local effects can be masked by the large-scale aggregation (Piniewski et al 2013a). They also noticed that the difference between the results achieved with one hydrological model under two or more different climate scenarios is sometimes larger than the difference between the results of different hydrological models or different management measures achieved by using one climate scenario (Arheimer et al 2012, Piniewski et al 2013a, 2013b. Hence, a large uncertainty is related to climate models and downscaling methods, which can be partly compensated for by applying an ensemble of different climate scenarios (Tebaldi and Knutti 2007, Huard 2011, Arheimer et al 2012.…”
Section: Discussionmentioning
confidence: 99%
“…Some regional trends can even be opposite to the overall trend for large areas (Arheimer et al 2012), and some local effects can be masked by the large-scale aggregation (Piniewski et al 2013a). They also noticed that the difference between the results achieved with one hydrological model under two or more different climate scenarios is sometimes larger than the difference between the results of different hydrological models or different management measures achieved by using one climate scenario (Arheimer et al 2012, Piniewski et al 2013a, 2013b. Hence, a large uncertainty is related to climate models and downscaling methods, which can be partly compensated for by applying an ensemble of different climate scenarios (Tebaldi and Knutti 2007, Huard 2011, Arheimer et al 2012.…”
Section: Discussionmentioning
confidence: 99%
“…Physically-based hydrological models are more suitable for simulations of basin response to a changing climate than empirical or conceptual models which rely more heavily on parameters calibration (Ragettli and Pellicciotti 2012). However, problems with a priori estimation of model parameters make physically-based hydrological models difficult to apply, while conceptual models are often argued to be a more practical alternative (Piniewski et al 2013). Parameters employed in hydrological models (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is often assumed that spatially explicit distributed hydrological models are more suited to predict the effects of changing environmental conditions (Beven and Binley 1992). The use of semi-distributed and distributed hydrological models in climate change impact analysis is increasing all the time (Maurer et al 2010, Piniewski et al 2013. The Soil and Water Assessment Tool (SWAT) model is used in this study.…”
Section: Introductionmentioning
confidence: 99%
“…Fowler et al, 2007;Kundzewicz & Stakhiv, 2010;Teng et al, 2012;Wilby, 2010). More recent studies focused on specific methodological problems in this procedure, namely on scale effects (Piniewski et al, 2013), rainfall statistics (Langousis et al, 2016), and hydro-meteorological extremes (Madsen et al, 2014;Tofiq & Guven, 2014;Sunyer et al, 2015). The results of these studies have confirmed the applicability of linking GCMs to hydrological models via RCMs.…”
Section: Introductionmentioning
confidence: 74%